The Effect of Implementing the Poster Session Learning Strategy Assisted by Audio-Visual Media on Fourth-Grade Students’ Interest and Learning Outcomes in Listening to Descriptive Texts at SDN Fatufia, Morowali Regency - Novita Lotong; Ida Nuraeni; Ulfah Ulfah (Journal of Educational Sciences, 2026)
This study aims to examine the effect of the poster session learning model assisted by audio-visual media on students’ learning interest and learning outcomes. This research employed a quantitative approach with a quasi-experimental design using a non-equivalent control group design. The sample consisted of an experimental class and a control class. Data were collected using a learning interest questionnaire and a learning outcomes test. Data were analyzed using Multivariate Analysis of Variance (MANOVA). The results revealed a significant effect of the poster session learning model assisted by audio-visual media on students’ learning interest and learning outcomes simultaneously (Wilks’ Lambda = 0.412; F(2,37) = 26.873; p < 0.05). Partially, the model also had a significant effect on both dependent variables. Therefore, this learning model can be considered an effective alternative to improve the quality of elementary education.